TRANSFORMATION OF THE PARTY SYSTEM OF SPAINAT NATIONAL AND REGIONAL LEVELS:COMPARATIVE ANALYSIS - Andrey Baranov (Ибероамериканские тетради)
The article reveals the transformation of the party system of Spain in 2014 - 2017. Similarities and differences in the crisis of the party system at the national and regional levels are revealed (on the materials of Catalonia). Attention is focused on changes in the social base of political parties and party commitment of voters, on applied strategies of inter-party competition.